First evaluation of neustonic microplastics in the Macaronesian region, NE Atlantic. (April 2020) - Herrera, A.; Raymond, E.; Martínez, I.; Álvarez, S.; Canning-Clode, J.; Gestoso, I.; Pham, C.K.; Ríos, N.; Rodríguez, Y.; Gómez, M.
Abstract: Marine microplastic pollution is an issue of great concern nowadays since high concentrations have been detected in the ocean, mainly in the subtropical gyres that accumulate this type of debris. The long-term effects of this pollution on ecosystems and marine biota are still unknown. The aim of this study is to quantify and characterise microplastics and neustonic zooplankton in sub-surface waters of the Macaronesian region, an area that has been little studied to date. Our results show a great variability in the concentration of microplastics with values between 15, 283 items/km 2 in Los Gigantes (Tenerife, Canary Islands) and 1, 007, 872 items/km 2 in Las Canteras (Gran Canaria, Canary Islands). The main types of debris found were plastic fragments and fibres. The abundances of neustonic zooplankton were also very variable between the different sampling areas, being the main components copepods and eggs. Regarding the microplastics-zooplankton ratio, values were obtained between 0.002 and 0.22. In Las Canteras, the highest accumulation zone, was found twice as much microplastics as zooplankton for the 1–5 mm fraction in dry weight. These values highlight the potential hazard of microplastics – and its associated chemical contaminants – for marine biota, especially for large filter feeders. Graphical Abstract: Unlabelled Image Highlights: Values of more than 1 million particles of microplastics per square kilometre were found. Most of the debris were plastic fragments and fibres. The microplastics-zooplankton abundance ratio was very variable. Microplastics-zooplankton abundance reached maximum values of 0.22. Twice as much plastic as zooplankton was found in the area of greatest accumulation.